How to Ask the Right Question and Find the Right Answer: Clinical Research for Transplant Nephrologists - Rodríguez-Ramírez, Sonia; Kim, S. Joseph (Frontiers in Immunology, 2022)
Clinical research is about asking and answering questions. Before solutions relevant to clinical problems can be sought, clinicians must frame questions in ways that are answerable using the methods of clinical research. Different types of questions are best answered using specific study designs. Each design has inherent strengths and limitations. In this review article, we provide an approach to asking answerable clinical research questions, review the major study designs, describe their strengths and weaknesses, and link the study designs to their intended purposes.